2013
DOI: 10.1128/jcm.03121-12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CHROMagar STEC and STEC O104 Chromogenic Agar Media for Detection of Shiga Toxin-Producing Escherichia coli in Stool Specimens

Abstract: The performance of CHROMagar STEC and CHROMagar STEC O104 (CHROMagar Microbiology, Paris, France) media for the detection of Shiga toxin-producing Escherichia coli (STEC) was assessed with 329 stool specimens collected over 14 months from patients with suspected STEC infections (June 2011 to August 2012). The CHROMagar STEC medium, after an enrichment broth step, allowed the recovery of the STEC strain from 32 of the 39 (82.1%) Shiga toxin-positive stool specimens, whereas the standard procedure involving Drig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 39 publications
2
36
1
Order By: Relevance
“…The STEC isolation rate of 10.5% in this study is higher compared to a study done in Morogoro region within the same country but close to a prevalence of 8.4% report in a study done in Nigeria (Raji et al, 2008;Onanuga et al, 2014). The observed differences in prevalence can be due to the isolation methods used in these studies whereby the present study used the current recommended culture method for STEC screening (Gouali et al, 2013) in contrast to other studies that used molecular methods. The overall prevalence of pathogenic bacteria causing diarrhoea in the studied population was 14.5% which is lower compared to 22.9% and 35.7%, previously reported in a studies conducted at Tanzanian National (Moyo et al, 2007) and Regional hospitals (Vargas et al, 2004).…”
Section: Discussioncontrasting
confidence: 54%
“…The STEC isolation rate of 10.5% in this study is higher compared to a study done in Morogoro region within the same country but close to a prevalence of 8.4% report in a study done in Nigeria (Raji et al, 2008;Onanuga et al, 2014). The observed differences in prevalence can be due to the isolation methods used in these studies whereby the present study used the current recommended culture method for STEC screening (Gouali et al, 2013) in contrast to other studies that used molecular methods. The overall prevalence of pathogenic bacteria causing diarrhoea in the studied population was 14.5% which is lower compared to 22.9% and 35.7%, previously reported in a studies conducted at Tanzanian National (Moyo et al, 2007) and Regional hospitals (Vargas et al, 2004).…”
Section: Discussioncontrasting
confidence: 54%
“…Consequently, parallel testing would improve E. coli 0157:H7 detection if one of the two media tested, Fluorocult or CT-SMAC, were used in combination with another medium that produced far fewer false-positive results. Rainbow agar, Biosynth culture media, and CHROMagar have been reported to produce fewer false-positive results (14,26). The need for a second medium is supported by the need to detect sorbitolfermenting E. coli 0157:H7 strains (15,21,43).…”
Section: Discussionmentioning
confidence: 99%
“…CHROMagar O157 detects O157 serogroups, and CHROMagar STEC detects both O157 and the six most common STEC serogroups other than O157 isolated in the United States (O26, O45, O103, O111, O121, and O145). This product is labeled for research use only in the United States, but a recent study demonstrated that CHROMagar STEC had a sensitivity of 89.1% and specificity of 86.7% (272). In HardyChrom SS Isolation of Salmonella (black on this medium) and Shigella (teal on this medium) Inositol-brilliant green-bile salt Isolation of P. shigelloides (white to pink on this medium) (not part of routine setup unless requested) MacConkey agar with sorbitol (SMAC) or cefixime-tellurite SMAC (CT-SMAC)…”
Section: Specimen Processingmentioning
confidence: 99%